2021
DOI: 10.3389/fimmu.2021.702156
|View full text |Cite|
|
Sign up to set email alerts
|

Podoplanin Drives Motility of Active Macrophage via Regulating Filamin C During Helicobacter pylori Infection

Abstract: Podoplanin (Pdpn) is a mucin-type transmembrane protein that has been implicated in multiple physiological settings including lymphangiogenesis, platelet aggregation, and cancer metastasis. Here, we reported an absence of Pdpn transcript expression in the resting mouse monocytic macrophages, RAW264.7 cells; intriguingly, a substantial upregulation of Pdpn was observed in activated macrophages following Helicobacter pylori or lipopolysaccharide stimulation. Pdpn-knockout macrophages demonstrated intact phagocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 56 publications
3
19
0
Order By: Relevance
“…They are responsible for the polarization of T H 1 via secretions of IL-12 and IL-23 [ 56 ]. The importance of macrophages in H. pylori infection is highlighted by their marked increases in inflammatory markers, cell motility [ 57 ], and infiltration into the peritoneum as early as 2 days post-infection [ 58 ]. Furthermore, transient removal of CD11b + macrophage population was identified to reduce gastric pathology in H. pylori infected mice without altering the bacterial load, implying its critical role in gastric pathology [ 59 ].…”
Section: Innate Immune Cell Activation and Suppression By H...mentioning
confidence: 99%
“…They are responsible for the polarization of T H 1 via secretions of IL-12 and IL-23 [ 56 ]. The importance of macrophages in H. pylori infection is highlighted by their marked increases in inflammatory markers, cell motility [ 57 ], and infiltration into the peritoneum as early as 2 days post-infection [ 58 ]. Furthermore, transient removal of CD11b + macrophage population was identified to reduce gastric pathology in H. pylori infected mice without altering the bacterial load, implying its critical role in gastric pathology [ 59 ].…”
Section: Innate Immune Cell Activation and Suppression By H...mentioning
confidence: 99%
“… 37 Cheok et al also proposed that during Helicobacter pylori infection, podoplanin drives motility of active macrophages via regulating Filamin C, a member of actin-crosslinking protein family that stabilizes and links actin web to the cell membrane. 39 , 40 They demonstrated that podoplanin may promote Filamin C transactivation through interacting with the ERM complex and activating Rho GTPase signaling pathway, but further investigation is required to confirm this notion. 39 …”
Section: Podoplanin Expression In the Innate And Adaptive Immune Systemsmentioning
confidence: 99%
“… 39 , 40 They demonstrated that podoplanin may promote Filamin C transactivation through interacting with the ERM complex and activating Rho GTPase signaling pathway, but further investigation is required to confirm this notion. 39 …”
Section: Podoplanin Expression In the Innate And Adaptive Immune Systemsmentioning
confidence: 99%
“…Targeting H. pylori-host interaction has also seen major advancement, especially in the alleviation of chronic inflammation. It has been identified that H. pylori induces expression of an inflammatory protein, podoplanin, via LPS to induce strong proinflammatory IL-1β secretion from macrophages [88]. Podoplanin has been proposed as a treatment target in chronic inflammatory rheumatoid arthritis [89].…”
Section: Targeting H Pylori Virulence and Pathogenesis In Treatment And Vaccine Developmentmentioning
confidence: 99%